Ictal phase-amplitude coupling as a biomarker for seizure onset zone in neocortical epilepsy - Nishioka, Kazuki; Iimura, Yasushi; Mitsuhashi, Takumi; Suzuki, Hiroharu; Ueda, Tetsuya; Nomura, Kazuki; Miao, Yao; Tanaka, Toshihisa; Otsubo, Hiroshi; Sugano, Hidenori; Kondo, Akihide (Frontiers in Neurology, 2025)
ObjectiveTo assess ictal phase–amplitude coupling (PAC) dynamics during seizure generation and explore whether ictal PAC analysis can help identify the seizure onset zone (SOZ) in neocortical epilepsy.MethodsWe analyzed ictal intracranial electroencephalography recordings from 22 seizures in six patients with drug-resistant neocortical epilepsy who achieved International League Against Epilepsy Class I outcomes following resection surgery. PAC strength was quantified using the modulation index (MI), computed by coupling the amplitude of high-frequency bands (ripples: 80–200 Hz; fast ripples: 200–300 Hz) with the phase of slow-wave bands (1–2 Hz, 2–3 Hz, 3–4 Hz and 4–8 Hz). MI values were compared across SOZ, peri-SOZ (adjacent electrodes), and non-SOZ regions. Localization accuracy was evaluated using the area under the curve (AUC) from receiver operating characteristic curve analysis.ResultsAcross all PAC between ripples and slow wave bands, MI values were significantly higher in the SOZ compared to the peri-SOZ and non-SOZ regions (p < 0.001). During the late phase of seizure onset, MIRipples/4–8 Hz was also significantly higher in the peri-SOZ region than in the non-SOZ region (p < 0.001). MIRipples/4–8 Hz (AUC: 0.853) and MIRipples/3–4 Hz (AUC: 0.846) demonstrated strong SOZ localization performance. MIRipples/3–4 Hz distinguished SOZ from peri-SOZ (AUC: 0.800).ConclusionElevated MI during seizure onset accurately localized the SOZ in neocortical epilepsy. Ictal PAC may be a useful biomarker for identifying SOZ in neocortical epilepsy.